PEMBELAJARAN SOSIOLOGI BERBASIS MEDIA ELEKTRONIK DI SMA NEGERI 1 PEMANGKAT - Noviandy, Haris; Sulistyarini, Sulistyarini; Al Hidayah, Riama (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract This research was to found out the sociology lesson based on electronic media at SMA Negeri 1 Pemangkat. The research approach was qualitative approach with descriptive approach method. The technique of data collection were observation, interview, and study documentation. The analysis in this research presented in qualitative descriptive using 5 informants, included the sociology teachers of Class X, XI and XII, also three active students representing each classes of Class X, XI, and XII on lesson based on electronic media at SMA Negeri 1 Pemangkat. The result showed that the cognitive aspects gave sociology lesson based on electronic media such impacts on students in order to found out and reviewed the lesson using electronic media also gave impacts on students learning result that using electronic media. In motivation aspects, electronic media encouraged students to studied and gave impacts on students' actions so it made students more focus on the lesson and students found themselves the learning material without instruction from the teacher. In imaginative aspects, electronic media generated students' imagination in searching material with pictures and videos, with electronic media students are easier to imagine the things that related with the material in their circumstances. Keywords: Cognitive, Electronic Media, Imaginative, Motivation